SAT0562 ADDITIONAL BENEFIT OF ULTRASOUND TO THE EARLY DIAGNOSIS OF PSORIATIC ARTHRITIS. (13th June 2020) - Geng, Y.; Cope, A.; Subesinghe, S.; Galloway, J.; Zhang, Z.; Kirkham, B.
Abstract : Background: Being an inflammatory disease of joint, spine or enthesis is the premise of the CASPAR diagnostic criteria for psoriatic arthritis (PsA). Traditionally, the assessment of local inflammation in joint, enthesis and tendon relies on physical examinations. But multiple studies have demonstrated that ultrasound (US) is capable of detecting subclinical inflammation as well as non-inflammatory lesions. Objectives: To compare the capabilities of physical examination and US findings in the diagnosis of early PsA, and further identify the US features which are most valuable for the diagnosis of PsA. Methods: 66 patients with suspected PsA or early PsA (disease duration< 2 years) due to psoriasis with joint pain or seronegative inflammatory arthritis were enrolled and further assessed by both physical examination and ultrasound (US).Tender and swollen joint counts based on 68/66 joints, tender tendons, enthesitis (14 entheses) and dactylitis (20 digits) count were collected by physical examination. Abnormalities of peripheral joints, entheses and tendons were also evaluated by US. New bone formation was evaluated by hand X-ray. The diagnostic capacity of CASPAR criteria based on US and based on physical examination were compared. The diagnosis value of US features as well as clinical characteristics were analyzed. The clinical diagnosis of PsA by the expert panel was taken as the standard. Results: CASPAR criteria based on US showed a higher specificity than those based on physical examination (96.7% vs. 53.3%) with a bit decrease of sensitivity (91.7% vs. 97.2%). 36 patients were eventually diagnosed as PsA and 30 patients were non-PsA. Gender distribution, mean age and disease duration were equally distributed in two groups of patients. Dermatology Life Quality Index (DLQI) was higher in PsA patients than non-PsA patients. Significantly more patients had nail change and new bone formation on hand X-ray in PsA patients than in non-PsA patients (69.4% vs. 26.7%, P =0.001 and 66.7% vs. 13.3%, P <0.001 respectively). Significantly higher frequencies of synovitis/synovium hypertrophy, tenosynovitis and enthesitis were found in PsA patients than non-PsA patients (58.3% vs 20.0%, P =0.002, 38.9% vs 3.3%, P =0.001 and 52.8% vs 13.3%, P =0.002, respectively). Logistic regression analysis showed that nail change (OR=25.1, P=0.007), new bone formation on X-ray (OR=33.1, P=0.003), tenosynovitis on US (OR=149.1, P=0.003) and enthesitis on US (OR=39.2, P=0.008) were independent risk factors for predicting the diagnosis of PsA. Conclusion: US increased the specificity of CASPAR criteria compared with physical examination. Combined nail change, new bone formation on X-ray, tenosynovitis and enthesitis on US improved the diagnosis of early PsA. References: [1]Polachek A, Cook R, Chandran V, et al. The association between sonographic enthesitis and radiographic damage in psoriatic arthritis. Arthritis Res Ther 2017; 19(1): 189. [2]Faustini F, Simon D, Oliveira I, et al. Subclinical joint inflammation in patients with psoriasis without concomitant psoriatic arthritis: a cross-sectional and longitudinal analysis. Ann Rheum Dis 2016; 75(12): 2068-74. Acknowledgments: The author thank all the colleagues in the department of Rheumatology of Guy's hospital. Disclosure of Interests: None declared